Encontrar temas en escritura creativa sobre la preservación ambiental para mejorar las estrategias de enseñanza: un caso de estudio en una escuela de primaria de Colombia - Suárez Ballesteros, Camilo Arturo; Bernal Camargo, María Claudia Esperanza; Nidia Yaneth Torres Merchán (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2021)
In this research, essays on trees preservation of fourth grade students (elementary school from Colombia) were evaluated with Latent Dirichlet Allocation (LDA). The objective was extracting the fundamental topics, to understand the students’ behavior and awareness towards the environment from the creative writing. The computational results suggest the student’s reflections on environment preservation are focused on five main topics in: Teach-Learn to care for the environment, Explore-discover the environment, Well-being of the environment, Concern for the environment, and Restoration and conservation of the environment. This text analysis by LDA can complement the manual analysis of teachers, avoiding the veracity bias and allowing the enhancement of teaching strategies.